Development of Fruit-Based Waste Material as Bioflocculant for Water Clarification / Peck Loo Kiew and Kian Hen Chong - Peck, Loo Kiew; Kian, Hen Chong (Faculty of Mechanical Engineering Universiti Teknologi MARA (UiTM), 2017)
Access to clean water is the major priority in all countries in the world in which millions of humans and living organisms die due to contaminated water-related diseases every year. Flora and fauna particularly urban rivers are losing attraction due to the problem of high turbidity in the water resources. Sedimentation and filtration had been regarded as efficient approaches in tackling turbidity of wastewater. The primary objective of this research is to investigate the possibility of converting Malaysian natural resource wastes (fruit-based) into bioflocculants for the potential application in turbidity removal in wastewater treatment process. The coagulation-flocculation potential in treating turbid water of four different fruit wastes which were inclusive of banana peels, jackfruit peels, pomelo peels and papaya seeds were investigated. The results revealed that banana peels demonstrated the most effective turbidity removal at 70.78 % in relative to other fruit wastes, without optimization processes. Interestingly, after the bioflocculation treatment using banana peels, residual pH of the treated water was 6.73, which was very close to neutral pH at 7.0 and fall within the WHO recommended pH value for drinking water quality (6.5 - 8.5). This implies that with further optimization study to enhance the turbidity removal and appropriate disinfection, if need be, the treated water using banana peel is suitable for human consumption. The exploitation of naturally available resources or waste materials into bioflocculants in this research had shed some lights in the discovery of efficient, biodegradable and green flocculants as potential replacement to conventional synthetic chemical coagulants in reducing water turbidity.